2005
DOI: 10.1007/s10745-005-4746-0
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothesis-Based Approach to Landscape Change in Suðuroy, Faroe Islands

Abstract: Hovsdalur, an area delimited by the great cirques of upland central Su uroy, draining into the valley of the Hovsá and terminating in the east at the coastal amphitheatre of Hovsfjørdur, is a microcosm of the Faroes. The area contains the physical and economic features which characterize the greater part of the island group-mountain, valley, and coast, and marine, cultivation, and grazing environments. Data comprising mainly geomorphological, palynological, and pedological evidence, covering the period prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
0
28
1
Order By: Relevance
“…Conversely, geomorphological studies on Sandoy and elsewhere in the Faroes suggest that erosion rates have increased at many localities through the course of the second half of the Holocene, and the suggestion has been made that gullying within the peat could have focused the erosive power of runoff, leading to higher overall rates of sediment transport (cf. Solem 1986;Humlum & Christiansen 1998a, 1998bBragg & Tallis 2001;Edwards et al 2005).…”
Section: Implications Of Blanket Mire Expansion For Other Aspects Of mentioning
confidence: 99%
“…Conversely, geomorphological studies on Sandoy and elsewhere in the Faroes suggest that erosion rates have increased at many localities through the course of the second half of the Holocene, and the suggestion has been made that gullying within the peat could have focused the erosive power of runoff, leading to higher overall rates of sediment transport (cf. Solem 1986;Humlum & Christiansen 1998a, 1998bBragg & Tallis 2001;Edwards et al 2005).…”
Section: Implications Of Blanket Mire Expansion For Other Aspects Of mentioning
confidence: 99%
“…Barley is not indigenous to the Faroes and so must have been either grown or brought to the islands by humans. The possibility of small-scale barley cultivation is strengthened by the barley-sized pollen grains first appearing in the Faroes palaeoecological record in the mid first millennium AD (Hannon et al, 2000(Hannon et al, , 2005Edwards et al, 2005;Figure 1a). …”
Section: Resultsmentioning
confidence: 99%
“…Previous research on the contemporary literary source of De Mensura Orbis Terrae written by the Irish monk Dicuil c. AD 825, attested to ecclesiastical anchorites settling remote North Atlantic islands (Tierney, 1967), but the specific identification of the Faroes in the text is a subject of debate (Arge 1991;Debes, 1993;Thorsteinsson, 2005;Dugmore et al, 2010). Palaeoenvironmental reconstruction in the form of close-interval pollen analysis (Jóhansen, 1985;Hannon et al, 2000Hannon et al, , 2001Hannon et al, , 2005Edwards et al, 2005;Edwards and Borthwick, 2010), has also suggested that small-scale human settlement may have occurred in 5 th -6 th centuries cal AD. This early settlement was proposed through the 14 C dating of sediment layers containing the first appearance of barley-type pollen, at sites such as Heimavatn in the north of the island chain and Hov in the south (see Figures 1 and 2a).…”
Section: Introductionmentioning
confidence: 99%
“…Fenton, 1978;Simpson, 1997;Meharg et al, 2006) might have been used to augment such field systems -add ing nutrients as well as alleviating soil wet ness if mineralrich turves were in volv ed -there is no tradition of this. For soils associated with supposed older field systems in the Faroe Islands, the cultural en hance ment of soil depths did take place (Edwards et al, 2005;cf. Gear, 2003;Donald son et al, 2009), but not always mark ed ly so (Edwards and Borthwick, 2010).…”
Section: Introductionmentioning
confidence: 99%